THE EFFECT OF HUMAN RESOURCE COMPETENCY, INFORMATION TECHNOLOGY UTILIZATION, INTERNAL CONTROL SYSTEMS, AND WORK MOTIVATION ON THE QUALITY OF FINANCIAL REPORTS OF COMMUNITY HEALTH CENTERS IN THE CITY OF BALIKPAPAN - Eka Puji Lestari; Yunita Fitria (JASS (Journal of Accounting for Sustainable Society), 2026)
This study aims to examine and analyze the influence of human resource competencies, information technology utilization, internal control systems, and work motivation on the quality of financial reports of Community Health Centers in Balikpapan City. This study is a quantitative study and uses primary data collected directly through questionnaires. The sample in this study consisted of 113 employees in the financial department of community health centers. The sampling technique used saturated sampling or census sampling, which means that all members of the population were used as samples. This study used multiple linear regression analysis processed using the SPSS (Statistical Package for Social Science) version 25 analysis tool. The results of this study indicate that (1) human resource competence does not have a significant effect on the quality of financial reports, (2) the use of information technology has a positive and significant effect on the quality of financial reports, (3) the internal control system has a positive and significant effect on the quality of financial reports, (4) work motivation has a positive and significant effect on the quality of financial reports.